Evaluation of under- and post-graduate Dental students of Isfahan Faculty of Dentistry in relation to communication skills and professional ethics - Seyed Ebrahim Jabarifar; Fakhrisadat Khalifesoltani; Kobra Hoseinpour; Homeira Shamir; Firozeh Nilchian (Isfahan University of Medical Sciences, 2012)
Abstract Introduction: Communication and professional ethics competencies are crucial in providing dental health care. Research has shown that teaching these competencies and patient rights to dental students is necessary. The aim of this study was to evaluate attitudes of under- and post-graduate dental students of Isfahan Faculty of Dentistry in relation to communication skills, professional ethics and patient rights.Materials and Methods: Sixty-one under- and post-graduate dental students were randomly selected for the purpose of this study, who voluntarily completed a relevant questionaire. Psychometric characteristics, face validity and internal consistency of the questionaire content were tested in a pilot study so that the questionnaire could be revised. Data was analyzed by SPSS 11.5 using t-test, one-way ANOVA, and Kruskal-Wallis and Mann-Whitney U tests (α=0.05). Results: Cronbach's alpha cofficient for communication and professional ethics was 0.969, which was considered favorable. Mean and standard deviation of communication skills and professional ethics competencies in under- and post-graduate dental students were 3.68±0.37 and 4.25±0.37, respectively. Mean scores of these competencies were significantly higher in post-graduate students compared to under-graduate students (p value = 0.03).Conclusion: The results showed that post-graduate students exhibit higher communication skills and professional ethics competencies in the management of their patients. Key words: Communication, Dental student, Professional ethics.